2023
DOI: 10.47853/fas.2023.e36
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of alloherpesvirus (cyprinid herpesvirus-2 and koi herpesvirus) and poxvirus (carp edema virus) identified from domestic and imported cyprinids in Korea

Abstract: Cyprinids are popular species for aquaculture worldwide, with Asia being a significant contributor to their production. In Korea, common carp (Cyprinus carpio), koi carp (Cyprinus rubrofuscus), and goldfish (Carassius auratus) are cultivated domestically and imported for ornamental or human consumption purposes. Among the viruses that infect cyprinids, cyprinid herpesvirus-2 (CyHV-2), koi herpesvirus (KHV, also known as cyprinid herpesvirus-3), and carp edema virus (CEV) are of particular concern as they cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Cyprinidae is a freshwater fish family with the highest species diversity, morphological and behavioral properties, and habitat requirements (Bain 2011); this family is crucial in the fishery industry in Asian countries (Jeong et al 2023), including Indonesia are 1,790 species recorded in this family (Fricke et al 2023), and 135 of these are found in Indonesia (Froese and Pauly 2023). The large number of Cyprinidae species makes this species potentially important as a food source for the community and ornamental fish trade (Samitra et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cyprinidae is a freshwater fish family with the highest species diversity, morphological and behavioral properties, and habitat requirements (Bain 2011); this family is crucial in the fishery industry in Asian countries (Jeong et al 2023), including Indonesia are 1,790 species recorded in this family (Fricke et al 2023), and 135 of these are found in Indonesia (Froese and Pauly 2023). The large number of Cyprinidae species makes this species potentially important as a food source for the community and ornamental fish trade (Samitra et al 2019).…”
Section: Discussionmentioning
confidence: 99%